New Cognitive Neurotechnology Facilitates Studies of Cortical–Subcortical Interactions. Issue 9 (September 2020) - Min, Byoung-Kyong; Hämäläinen, Matti S.; Pantazis, Dimitrios
Abstract : Most of the studies employing neuroimaging have focused on cortical and subcortical signals individually to obtain neurophysiological signatures of cognitive functions. However, understanding the dynamic communication between the cortex and subcortical structures is essential for unraveling the neural correlates of cognition. In this quest, magnetoencephalography (MEG) and electroencephalography (EEG) are the methods of choice because they are noninvasive electrophysiological recording techniques with high temporal resolution. Sophisticated MEG/EEG source estimation techniques and network analysis methods, developed recently, can provide a more comprehensive understanding of the neurophysiological mechanisms of fundamental cognitive processes. Used together with noninvasive modulation of cortical–subcortical communication, these approaches may open up new possibilities for expanding the repertoire of noninvasive cognitive neurotechnology. Highlights: Advances in neuroimaging methods, combined with new brain magnetic sensors and neuromodulatory technology, open important new avenues for future research. Recent studies in brain electrophysiological imaging offer compelling evidence that, under favorable circumstances, localizing brain signals is possible, even from deep brain structures. Methodological and technological developments have opened new possibilities for comprehensive investigation of cortical–subcortical temporal dynamics. A cortical–subcortical integrative approach is essential for understanding human cognition and the mind–brain relationship.